Management of diabetic foot ulcers: polyherbal formulations and novel delivery systems for herbal active components - Feng, Bowen; Dou, Jinjin; Li, Yongji; Wang, Yihan; Wu, Changmei; Lan, Xiaodong; Su, Yi; Zhang, Xiwu (Frontiers in Pharmacology, 2025)
Diabetic foot ulcers (DFUs) represent devastating complications associated with high risks of amputation and mortality. The complex pathophysiology of the wound microenvironment and systemic involvement render conventional therapies costly and limited in effectiveness. Consequently, there is an urgent demand for the development of effective and comprehensive therapeutic and management strategies. Herbal medicines and their formulations can transform DFU management from passive debridement to active regeneration through multi-target synergy and holistic intervention, offering low-cost and safe alternatives. Integrating herbal active components with polymeric materials enables the development of novel delivery systems and tissue-engineered scaffolds. This interdisciplinary approach is emerging as a promising therapeutic strategy in regenerative medicine and dermal engineering. This paper compares cellular healing mechanisms in DFUs and normal wounds, elucidates the mechanisms of action of herbal medicines and their formulations in treating DFUs, and synthesizes the applications of novel delivery systems for herbal active components in DFU therapy.